Football : stats, facts, and figures - Mikoley, Kate (Mikoley, Kate. Do math with sports stats!, 2018)
Introduces the game of football by examining some of the key statistics and math elements involved, such as how measuring time, individual and team statistics, and field measurements. Includes color photographs, text-dependent math questions, a glossary of terms, and an index.